The relationship between the determinants of executive remuneration in South African state-owned enterprises - Frans Maloa (SA Journal of Human Resource Management, 2020)
Orientation: Research on executive remuneration should be able to indicate the necessary elements and dimensions at work when deciding on an executive’s package.